Catch-Up Growth, Habits, Oil Depletion, and Fiscal Policy Lessons From the Republic of Congo - Carcillo, Stéphane (International Monetary Fund, 2007)
In a number of oil producing countries, oil revenue accounts for the majority of government revenue, but is expected to be depleted in a relatively short time frame. Ensuring that fiscal policy is on a sustainable path is thus a high priority, but political and social adjustment costs create incentives to delay fiscal consolidation. This paper estimates how the permanently sustainable non-oil primary deficit (PSNOPD) depends on the speed of consolidation, using an optimization model with habit formation. Realism is added by allowing for negative growth-adjusted interest rates during a temporary period of catch-up growth. Applied to the Republic of Congo, this approach leads to the following conclusions: (i) the current fiscalpolicy stance is unsustainable; (ii) social adjustment costs justify spreading the bulk of the adjustment over five years; and (iii) the slower the adjustment, the lower the PSNOPD level